2017
DOI: 10.1128/iai.00420-17
|View full text |Cite
|
Sign up to set email alerts
|

Bacteroides fragilis Enterotoxin Induces Formation of Autophagosomes in Endothelial Cells but Interferes with Fusion with Lysosomes for Complete Autophagic Flux through a Mitogen-Activated Protein Kinase-, AP-1-, and C/EBP Homologous Protein-Dependent Pathway

Abstract: Bacteroides fragilis enterotoxin (BFT), a virulence factor of enterotoxigenic B. fragilis (ETBF), plays an essential role in mucosal inflammation. Although autophagy contributes to the pathogenesis of diverse infectious diseases, little is known about autophagy in ETBF infection. This study was conducted to investigate the role of BFT in the autophagic process in endothelial cells (ECs). Stimulation of human umbilical vein ECs (HUVECs) with BFT increased light chain 3 protein II (LC3-II) conversion from LC3-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…N-(6-Methyl-2-benzothiazolyl)-2-[ (3,4,6,7- Purification of BFT and cell culture conditions. BFT was purified from culture supernatants of a toxigenic strain of ETBF (ATCC 43858) as described previously (18,26,34). The purity of the BFT preparations was verified, as they appeared as a single band on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels.…”
Section: Methodsmentioning
confidence: 99%
“…N-(6-Methyl-2-benzothiazolyl)-2-[ (3,4,6,7- Purification of BFT and cell culture conditions. BFT was purified from culture supernatants of a toxigenic strain of ETBF (ATCC 43858) as described previously (18,26,34). The purity of the BFT preparations was verified, as they appeared as a single band on sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) gels.…”
Section: Methodsmentioning
confidence: 99%
“…Delayed apoptosis has been observed in BFT-exposed IECs [ 27 , 37 ]. These findings raise the possibility that the generation of signals for preventing apoptosis is evoked in BFT-treated IECs.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of experiments to demonstrate this hypothesis, we already reported that the enhanced expression of cellular inhibitor of apoptosis protein-2 attenuates the apoptosis in IECs [ 27 ]. In addition, BFT-induced heme oxygenase-1 (HO-1) upregulation is also closely connected with the suppression of apoptosis [ 37 ]. However, overexpression of HO-1 did not completely prevent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The final steps of autophagy are the fusion of an autophagosome and lysosome to form the autolysosome, and then the degradation of its inner membrane and internal cargos by lysosomal acid hydrolases. The core mechanisms of autophagosome trafficking and lysosomal fusion, and their regulation, are still unclear (Ko et al , ). The movement of lysosomes and endosomes has a decisive role in the fusion process to form autolysosomes, and is supported by microtubular motor proteins like myosin, kinesin, and dynein.…”
Section: Convergence Of Autophagy and Endocytosismentioning
confidence: 99%
“…In addition, levels of p62, LC3‐II, ATG5 and ATG12, proteins which are essential for autophagosome formation, increased when cells were treated with the Bacteroides fragilis enterotoxin (BFT). Like rapamycin, BFT promotes autophagosome formation via the fusion process, although rapamycin shows a greater influence on the fusion process (Ko et al , ). Heavy metals like cadmium are known to induce oxidative stress and autophagy, and accumulation of both cadmium and calcium ions block the autophagosome–lysosome fusion process (Liu et al , ).…”
Section: Convergence Of Autophagy and Endocytosismentioning
confidence: 99%